Improving Cotton Fiber Quality Through Strategic Sowing: Implications for Phosphorus Management from Experiments in Chato District, Tanzania - Jacob Shauri Tlatlaa; George Muhamba Tryphone; Eliakira Kisetu Nassary (Journal of Natural Fibers)
This study was conducted in Msilale Village, Chato District in Tanzania, to evaluate the influence of sowing dates and phosphorus levels on cotton fiber quality. The study was established according to a factorial trial, with varying sowing dates (25th November 2022, 15th December 2022 and 4th January 2023) and phosphorus levels (control, 20 kg P ha−1, 40 kg P ha−1, 60 kg P ha−1). Results revealed that early planting had a statistically significant (p < .001) effect on fiber cotton quality, including spinning coefficient index, fiber length, fiber strength, uniformity index, short fiber content, and grade/color. Early sowing dates (25th November 2022 and 15th December 2022) consistently produced superior fiber quality, including spinning coefficient index (156.5 and 148.4), moisture content of the fiber (7.8% and 7.7%), micronaire (3.5 μg/inch), upper half mean length (1.2 cm), uniformity index (84.6% and 84.2%) and shorter fiber (6.8% and 7.0%) relative to late sowing (4th January 2023). Conversely, phosphorus levels did not significantly (p > .05) impact these parameters within the tested range. This research underscores the critical role of selecting appropriate sowing dates for cotton cultivation to achieve better fiber quality.